The little drummer boy - Keats, Ezra Jack.; Davis, Katherine, 1892-; Onorati, Henry; Simeone, Harry; Davis, Katherine, 1892- (New York : Aladdin Books, 1987)
An illustrated version of the Christmas carol about the procession to Bethlehem and the offer of a poor boy to play his drum for the Christ Child. Music for the song appears in the back of the book.
Reprint. Originally published : The little drummer boy / Katherine Davis. New York : Macmillan, 1968.
School Library Journal.
Booklist.
Horn Book.
2.9
K-3
Keywords: Carols -- Texts; Christmas music; Carols; Christmas music; Carols; Christmas music; Carols; Christmas music